From A to Zine : Building a Winning Zine Collection in Your Library. - Bartel, Julie (ALA Editions, 2004)
Libraries eager to serve the underserved teen-to-twenty-year-old market can make the library a cool place to hang out. All it takes are zines, according to the author, young adult librarian Julie Bartel. Zines and alternative press materials provide a unique bridge to appeal to disenfranchised youth, alienated by current collections. For librarians unfamiliar with the territory, or anxious to broaden their collection, veteran zinester Bartel establishes the context, history, and philosophy of zines, then ushers readers through an easy, do-it-yourself guide to creating a zine collection, includ.